2007
DOI: 10.1379/csc-220r.1
|View full text |Cite
|
Sign up to set email alerts
|

SGT2 and MDY2 interact with molecular chaperone YDJ1 in Saccharomyces cerevisiae

Abstract: In Saccharomyces cerevisiae, Sgt2 was thought to be the homologue of vertebrate SGT (small glutamine tetratricopeptide repeat-containing protein). SGT has been known to interact with both Hsp70 and Hsp90. However, it was not clear whether Sgt2 might have a similar capacity. Here, we showed that Ssa1/Ssa2 (yeast heat shock cognate [Hsc]70), Hsc82 (yeast Hsp90), and Hsp104 coprecipitated with Sgt2 from yeast lysates. Another molecular chaperone, Ydj1, known to interact with Ssa1 and Hsc82, also coprecipitated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 46 publications
1
43
0
4
Order By: Relevance
“…The Sgt2 Dimer Binds a Single Copy of Get5 at a Canonical Ubl Interface-Yeast two-hybrid assays (7,14) and analytical SEC (5) indicated that the N terminus of Sgt2 and the Ubl domain of Get5 are necessary for binding between these two proteins; however, molecular details of this interaction remain to be defined. We used a nickel affinity pulldown assay to further characterize the complex.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Sgt2 Dimer Binds a Single Copy of Get5 at a Canonical Ubl Interface-Yeast two-hybrid assays (7,14) and analytical SEC (5) indicated that the N terminus of Sgt2 and the Ubl domain of Get5 are necessary for binding between these two proteins; however, molecular details of this interaction remain to be defined. We used a nickel affinity pulldown assay to further characterize the complex.…”
Section: Resultsmentioning
confidence: 99%
“…Additional yeast two-hybrid and pulldown assays demonstrated that an N-terminal construct of Sgt2 was necessary and sufficient for binding to Get5, and consequently Get4, in an interaction also dependent upon the Ubl domain of Get5 (7,14). A direct role for Sgt2 in the TA targeting pathway was shown by two independent genetic interaction analyses indicating a strong functional connection with other GET pathway members (23,24).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The GET4 and GET5 genes appear to be highly conserved, raising the possibility that their counterparts are present in the mammalian TM-recognition complex (see also Stefanovic and Hegde, 2007). Although Get4 has not been functionally characterized, Get5 has been found to associate with Sgt2, a factor involved in the coordination of several more ubiquitous chaperones such as Hsc70 and Hsp90 (Angeletti et al, 2002;Liou et al, 2007). Intriguingly, Get4 and Get5 have been suggested to associate with ribosomes on the basis of a proteomic analysis of yeast ribosomeassociated complexes (Fleischer et al, 2006).…”
Section: Get Pathway Of Er Integrationmentioning
confidence: 99%
“…Briefly, the pathway begins when Sgt2 recognizes the TMD of a nascent TA protein by its Met-rich C-terminal domain and then binds to a ubiquitin-like domain of Get5 via its N-terminal dimerization domain (11,12). The N-terminal region of Get5 (referred to as Get5N) then binds to the C-terminal region of Get4 to form a stable complex, predominantly through hydrophobic interactions (13).…”
mentioning
confidence: 99%